Exploring Attachment Dimensions in Individuals with Overweight or Obesity - Silvia Tempia Valenta; Sara Ventura; Silvia Garelli; Valentina Vicennati; Massimiliano Beneventi; Alessandro Agostini; Uberto Pagotto; Nicola Filippini (Behavioral Sciences)
Introduction. Obesity is a complex condition associated not only with physical health risks but also with social discrimination and a reduced quality of life (QoL). Psychological factors, including attachment styles, may play a role in emotional regulation and eating behaviors. According to attachment theory, insecure attachment is linked to difficulties in managing emotions and an increased likelihood of engaging in dysfunctional eating patterns. This study aimed to investigate the relationship between past and present attachment styles, binge-eating behaviors, and QoL scores in individuals with overweight or obesity (BMI ≥ 25 kg/m2) compared to those with a BMI in the normal weight range (18.5–24.9 kg/m2). Methods. A cross-sectional study evaluated 96 women with overweight/obesity and 96 women with normal weight. Psychological measures included the Parental Bonding Instrument (PBI), the Attachment Style Questionnaire (ASQ), the Binge Eating Scale (BES), and the Obesity-Related Well-being questionnaire (ORWELL 97). Data analysis included between-group comparisons of attachment dimensions and hierarchical regression to examine associations with the QoL score. Results. Participants with overweight/obesity showed less secure attachment (U = 5508, p = 0.019) and more avoidant attachment styles (U = 3825, p = 0.042) compared to participants with normal weight. Conversely, no significant differences were observed in PBI scores. Regression analysis revealed that attachment anxiety (B = 0.83, p = 0.009) and binge-eating behaviors (B = 0.57, p = 0.003) were significantly associated with a lower QoL. Conclusions. Obesity is associated with avoidant attachment in adulthood, but no differences were found in parental attachment when compared to individuals with normal body weight. Anxious attachment in individuals with obesity is strongly linked to reduced QoL, underlying the role played by attachment-related factors in the psychosocial challenges individuals often have to face.